The Role of Virtual and NonStandard Laboratory Experiences in the Development of Student’s Independent Work Skills - Zakir Makhsudovich Ataullayev (Genius Journals, 2022)
This article provides information on how students in chemistry classes can conduct chemical experiments with information and communication technologies, understand new material, conduct experiments with toxic chemicals, and use rare and expensive reagents in desired quantities. In addition, it is thought that such tasks as strengthening the studied topic and drawing independent conclusions from the results of experiments can be mastered in a short time. It also highlighted the importance of non-standard laboratory experiments with substances used in life in developing students' independent work skills in chemistry lessons in secondary schools
Keywords: Chemist; profession; doctor; interest; enthusiasm